Opting in or Opting out: The New Legal Process or Arbitration - Geraldine Szott Moohr (Washington University Law Quarterly, 1999)
Professor Krotoszynski suggests that judicial legitimacy has fallen victim to the expectations of multiple constituencies, who evaluate judicial competency on the basis of particular substantive results. These “outsider” constituencies— feminists, critical race scholars, queer theorists, critical legal studies scholars, and law and economics advocates— have effectively demonstrated the deficiencies in the judicial system. While applauding their contribution to a fairer and more just society, Professor Krotoszynski laments the damage to judicial credibility and the absence of common ground that makes dialogue across constituencies increasingly difficult. Taking a page from sporting events, he sees a newly defined legal process as our “best hope” for devising a legal system that multiple constituencies will find fair, thus restoring confidence in judicial determinations. Reflecting this preference, he expresses “grave doubts” about recommendations that cultural minorities and commercial entities embrace arbitration. My response comments on the new legal process and on the possible exodus to arbitration.
Keywords: Legal discourse; Arbitration & award; Dispute resolution (Law); Judicial process; Minorities